Physical Effort Ability in Counter Movement Jump Depending on the Kind of Warm-Up and Surface Temperature of the Quadriceps - Adamczyk, J. G.; Boguszewski, D.; Siewierski, M. (Baltic Journal of Health and Physical Activity, 2012)
Background: The aim of this research was an attempt at qualifying the influence of various kinds of warm-up on physical effort ability, as well as examining whether there exists any dependence between the surface temperature of the quadricipital muscle of the thigh and the power expressed with the height of counter movement jump (CMJ). Material/Methods: In the research thermographic imaging and dynamometric platform were used. The subjects performed the CMJ test in 3 separate sessions - without any warm-up and then after preparation (1st session - jogtrot; 2nd session - jogtrot and stretching exercises; 3 session - dynamic warm up exercises). Results: In the examined group there was no lineal dependence between the surface temperature of the quadriceps and the power expressed with the height of a jump. Regardless of the kind of the applied warm-up, subjects improved their own results in the CMJ test; however, no such regularity concerning the temperature rise on the surface of a muscle was observed. In a dynamic warm-up lower surface temperature of the quadriceps meant a higher value of CMJ (r=0.64; p Conclusions: The fact that highest values of a jump and surface temperature were attained after various kinds of warm-up permits supposing that finding individual forms of preparation for effort by an athlete, in order to increase the competition efficiency, is possible.